INTENSITY OF NITRIC OXIDE SYNTHESIS IN THE BLOOD OF RATS UNDER THE INFLUENCE OF SODIUM FLUORIDE - I.L. Kolisnyk (Проблеми екології та медицини)
The influence of fluoride ion as a chemical agent affects the metabolism, the change of which is manifested in functional and structural changes. The final stable metabolites of NO include nitrite and nitrate anions (NO2, NO3), the concentration of which serves as an indirect method for estimating the intensity of NO synthesis. The concentration of NO is a major factor in its numerical biological effects (regulatory, protective). At low NO concentrations, direct effects aimed at maintaining homeostasis, such as the vascular, respiratory, and nervous systems, predominate; at high concentrations of NO, indirect effects prevail, due primarily to the formation of peroxynitrite. It is known that when the rate of free radical reactions in the body increases, NO can react with a superoxide anion radical to form peroxynitrite, a highly reactive compound with destructive properties against proteins and lipids. Oral administration of FN to rats in doses of 1/10 and 1/100 DL50 leads to an increase in the content of nitrite and nitrate anions in the blood plasma during the first 30 days, which indirectly indicates excess production of nitric oxide, which in the initial stages of intoxication may play a compensatory role, but subsequently cause pathological reactions associated with the activation of oxidative stress. The decrease in nitrite and nitrate anions at the end of long-term action of FN indirectly indicates a decrease in nitric oxide generation, which may be associated, in particular, with an increase in peroxynitrite concentration due to the use of nitric oxide in reaction with superoxide anion radical and antioxidant deficiency.